2011
DOI: 10.1007/s10067-011-1887-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disease activity, pain, disability and treatments on fatigue in established rheumatoid arthritis

Abstract: We investigate a range of clinical factors and anti-rheumatic treatments, for their degree of association with rheumatoid arthritis (RA) fatigue in 557 patients. A range of clinical measures concerning disability, pain and disease activity together with drug history were recorded as part of routine clinical visits. Fatigue was measured using the Functional Assessment of Chronic Illness Therapy (FACIT-F) questionnaire. Spearman's correlation (p < 0.05) evaluated FACIT-F against the other clinical measures. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 19 publications
7
39
0
1
Order By: Relevance
“…Of the 3 PROs we evaluated, fatigue was the least likely to improve. Other studies have also found that fatigue is resistant to improvement during therapy 26, 27. Nevertheless, 38.5% of patients who remained on therapy in our study did experience a significant response in fatigue after 12 months of adalimumab treatment, in agreement with other studies of the effect of anti‐TNF agents, including adalimumab, on fatigue 28, 29.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 3 PROs we evaluated, fatigue was the least likely to improve. Other studies have also found that fatigue is resistant to improvement during therapy 26, 27. Nevertheless, 38.5% of patients who remained on therapy in our study did experience a significant response in fatigue after 12 months of adalimumab treatment, in agreement with other studies of the effect of anti‐TNF agents, including adalimumab, on fatigue 28, 29.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the interrelations between the outcomes and the relative importance of explanatory variables may also be influenced by the characteristics of the RA patients, including disease stage and activity [31]. The present study examined associations between PaGl, pain, and fatigue as scored on VAS in a well-characterized sample of DMARD-treated RA patients from the daily clinic initiating biological treatment due to active and uncontrolled disease activity.…”
Section: Discussionmentioning
confidence: 97%
“…Higher baseline fatigue is reported in patients with RA initiating TNF inhibitor therapy as opposed to traditional synthetic DMARDs (17,21), while a similar fatigue response to treatment among patients treated with either synthetic DMARDs or TNF inhibitors is also reported (17,22). It is not known if the nature and origin of fatigue or if the impact of synthetic DMARDs versus TNF inhibitors on fatigue differ at different stages of the disease (22). Despite the multitude of published studies on the efficacy of biologic DMARDs, few have measured fatigue with respect to TNF inhibitor therapies (17,23,24).…”
Section: Introductionmentioning
confidence: 96%
“…While a relationship between disease activity and fatigue is recognized, pain and TJC are also seen as predictors of fatigue in IA (17), so too are function and psychosocial variables (18 -20). Higher baseline fatigue is reported in patients with RA initiating TNF inhibitor therapy as opposed to traditional synthetic DMARDs (17,21), while a similar fatigue response to treatment among patients treated with either synthetic DMARDs or TNF inhibitors is also reported (17,22). It is not known if the nature and origin of fatigue or if the impact of synthetic DMARDs versus TNF inhibitors on fatigue differ at different stages of the disease (22).…”
Section: Introductionmentioning
confidence: 99%